ASPECTS OF NEWSPAPER LANGUAGE LEARNING - Bozorova Sabokhat Ramazonovna (Journals Park Publishing, 2022)
The newspaper, which was the first large, fast-moving network of mass media, plays an important role in the development of society. Changes in socio-political, economic and cultural life are reflected in it in the first place. The newspaper informs the public about the achievements in politics, economics, science and technology and culture, and plays an advocacy and organizational role. Language and style play an important role in the newspaper's fulfillment of such a responsible task. Scientific research on such a serious issue has scientifically substantiated the theoretical study of the media and propaganda as a science. This is the focus of our research.
Keywords: newspaper language; aspect; media